TEACHERS' PERCEPTIONS OF THE DEVELOPMENT OF ENGLISH LEARNING BOOKS BASED ON TPACK IN MADRASAH IBTIDAIYAH - Damanik, Emeliya Sukma Dara; Daulay, Sholihatul Hamidah (Auladuna: Jurnal Pendidikan Dasar Islam, 2025)
This study aimed to analyze teachers' perceptions of the development of English learning books based on TPACK in Madrasah Ibtidaiyah (MI). This study used a descriptive quantitative approach with a questionnaire as the instrument covering four dimensions: urgency and benefits, ease of development and implementation, availability of support, and impact on student learning outcomes. The research respondents were 10 MI teachers who taught English in Medan. The results of the analysis indicated that teachers' perceptions were generally positive, with the highest scores on the dimension of impact on student learning outcomes, followed by the urgency and benefits of TPACK-based books. However, the dimension of availability of support received the lowest score, indicating limitations in training, reference materials, and facilitation of collaboration in the development of these books. This study concludes that TPACK-based books have significant potential to improve the quality of English language learning in MI, but their success requires adequate institutional support.